Design of an integrated automation and control system using Petri nets: case study (2023)
Integrated automation and control system (IACS) based on the discrete events control using Petri nets (PN) that encompasses the design, analysis, and validation of models of industrial pumping systems are not commonly used. Our case study is the design, simulation, and initial implementation of a supervision system using GHENeSys PN and EROS software at the "San Juan" Pumping Station in Santiago de Cuba, Cuba. These tools allow describing the models of the states of the local automatic process and the operation of the Supervisor to consider the functions of Preventive Maintenance and Alarm Treatment. The IACS starts from the MatLab simulation of main control loops and later uses the GHENeSys extended hierarchical net to model a modularly structured integrated automation system that responds to synchronized functional demands. This methodology has the advantages of full hierarchical modularity from local control to production management, various modular verification and validation tools, and full IEC61131 compatibility. This reduces design errors and implementation time with increased integration efficiency.